PERANCANGAN ANIMASI 2D œJIKA KITA TAK PERNAH JADI APA-APA SEBAGAI MOTIVASI INSECURE AKAN MASA DEPAN - Annisa Nugraheni; Anung Rachman; Rendya Adi Kurniawan (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2023)
Every individual must have felt a feeling of insecurity. Insecure is linked to mental health conditions, one of which is anxiety. These feelings, if considered trivial, can cause individuals to hurt themselves. The purpose of this study is to raise the spirit and help reduce insecurity by watching motivational videos as a form of self-healing. This research uses the MDLC (Multimedia Life Development Cycle) method consisting of six stages, namely: Concept, Design, Material Collecting, Assembly, Testing, and Distribution. The result of this study is a 2D animation product entitled